Graphene-containing metallized silicon oxide composite material
A composite anode material with core particles coated in pyroclastic carbon, featuring specific Raman spectrum ratios, addresses the degradation issues of silicon-based anodes by enhancing cycle life and conductivity, enabling stable performance in high-power lithium-ion batteries.
Patent Information
- Application Number
- KR1020227043440
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-19
- Filing Date
- 2021-05-17
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2041-05-17
AI Technical Summary
Silicon-based anode materials in lithium-ion batteries suffer from rapid cycle life degradation, low charge-discharge rate characteristics, and substandard Coulomb efficiency due to extreme volume changes during charging and discharging, leading to electrical disconnection and unstable solid electrolyte interface formation, which limits their use in high-power applications.
A composite anode material comprising core particles of alkali metal or alkaline earth metal silicate coated with pyroclastic carbon, characterized by specific Raman spectrum ratios (I D /I G and I 2D /I G) to enhance cycle life stability and rate performance, is formed through spray-drying a mixture of these components.
The composite material significantly improves cycle life stability, maintaining over 90% capacity after 20 cycles and enhancing electrical conductivity, thereby addressing the limitations of silicon-based anodes in high-power applications.
Smart Images

Figure 112022133083770-PCT00004_ABST
Abstract
Description
Technology Field
[0001] Aspects of the present disclosure relate to a graphene-containing metallized silicon oxide composite active material, a cathode comprising the same, and a battery comprising the cathode. Background Technology
[0002] Lithium (Li) ion electrochemical batteries generally require materials that enable high energy density, high power density, and high cycling stability. Lithium-ion batteries are commonly used in a wide range of applications, including consumer electronics, wearable computing devices, military mobile equipment, satellite communications, spacecraft, and electric vehicles; they are particularly widely used in large-scale energy applications such as low-emission electric vehicles, renewable power plants, and stationary electric grids. Furthermore, lithium-ion batteries are at the forefront of next-generation wireless and portable communication applications. One or more lithium-ion batteries can be used to constitute batteries that function as power sources in these applications. However, as the number of applications requiring higher energy increases exponentially, research into lithium-ion batteries with much higher energy density, higher power density, higher charge-discharge rates, and longer cycle life is accelerating. Additionally, as the adoption of lithium-ion technology increases and applications shift toward higher current requirements, longer operating times, wider and higher power ranges, and smaller form factors, the need to expand today's energy and power densities continues to grow.
[0003] Silicon or silicon alloy anode materials are currently included in most long-term lithium-ion technology adoption roadmaps as a practical means to achieve higher energy and power densities. Silicon is a preferred anode active material for lithium-ion electrochemical battery applications, with a theoretical gravimetric capacity of approximately 4,200 mAh / g and a volumetric capacity of approximately 9,786 mAh / cm³ when fully lithiated. 3 Silicon is also a desirable alternative to current graphite-based anodes because its high lithium storage capacity can exceed seven times that of graphite. However, the market adoption of silicon-based anodes for use in lithium-ion batteries has been hampered by rapid cycle life degradation, low charge-discharge rate characteristics under high power requirements, and substandard or insufficient Coulomb efficiency, all of which can be caused by extreme anode volume changes during charging and discharging (volume expansion of up to 400% has been recorded). The cycle life degradation of silicon-based alloys is well known and can be divided into two basic mechanisms: (1) electrical disconnection and (2) an unstable solid electrolyte interface (SEI) that leads to increased lithium-ion consumption and impedance. High-rate characteristics and Coulomb efficiency are also impaired by these mechanisms. Electrical disconnection occurs along with significant volume fluctuations during charging and discharging due to large volume changes during lithiation and delithiation.
[0004] These large volume changes can cause the pulverization of silicon particles (cracking and fracture due to stress) and the loss of electrical contact between these active silicon particles. As a result, an electrochemical cell with low power capacity and rapid capacity decline is produced. The cracking and fracture introduced into mechanism (1) further degrades cell performance by subsequently promoting mechanism (2), which is an unstable SEI. Because the new Si surface is exposed to the electrolyte solvent due to the cracking and fracture, additional SEI formation occurs, and lithiated compounds are deposited on the new Si surface. During charge / discharge cycles, the insulating SEI layer also becomes thicker, further degrading the capacity and cycling stability of the Si anode and impairing charge / discharge rate characteristics and Coulomb efficiency.
[0005] The continuous and new growth of the SEI layer is due to available Li + The amount of available electrolyte is gradually depleted due to side reactions with the electrolyte solvent and salt(s), and the overall performance of the electrochemical cell is degraded. Therefore, the use of silicon-based anodes in applications requiring high charge / discharge rates of electrochemical cells is severely limited due to the high ohmic and ionic contributions to polarization caused by these mechanisms.
[0006] Therefore, silicon-based electrode materials with improved primary cycle efficiency and cycle life are required.
[0007] Therefore, there is a need for an improved anode active material for use in electrochemical cells that includes a carbon material with defined quality characteristics that favorably influence the cycle characteristics of the electrochemical cell. More specifically, there is a need for an improved silicon-based composite anode material that includes low-defect non-layered carbon that enables cycle life stability, energy density, and rate performance of lithium-ion electrochemical cells. means of solving the problem
[0008] According to various embodiments of the present disclosure, active material composite particles comprise a core particle comprising an alkali metal or alkaline earth metal silicate and a coating disposed on the surface of the core particle. The coating comprises pyroclastic carbon, wherein the pyroclastic carbon is: 1330 cm⁻¹ -1 to 1360 cm -1 Peak intensity (I) at wavenumbers between D D band having ); 1580 cm -1 up to 1600 cm -1 Peak intensity (I) at wavenumbers between G G band having ); and 2650 cm -1 to 2750 cm -1 Peak intensity (I) at wavenumbers between 2D Having a Raman spectrum with a 2D band having ), where I D / I G The ratio of is in the range of greater than 0 to about 1.1, and I 2D / I G The ratio is in the range of about 0.4 to about 2.
[0009] According to various embodiments of the present disclosure, a method for forming active material composite particles comprises: forming a mixture comprising core particles comprising an alkali metal or alkaline earth metal silicate and pyroclastic carbon; and spray-drying the mixture to form composite particles comprising core particles coated with pyroclastic carbon. The pyroclastic carbon is: 1330 cm -1 to 1360 cm -1 Peak intensity (I) at wavenumbers between D D band having ); 1580 cm -1 up to 1600 cm -1 Peak intensity (I) at wavenumbers between G G band having ); and 2650 cm -1 to 2750 cm -1 Peak intensity (I) at wavenumbers between 2D It has a Raman spectrum with a 2D band having ). I D / I G The ratio of is in the range of greater than 0 to about 1.1, and I 2D / I G The ratio is in the range of about 0.4 to about 2.
[0010] Other key features and advantages of the present invention will become apparent to those skilled in the art upon reviewing the following drawings, detailed description, and appended claims. Brief explanation of the drawing
[0011] FIG. 1a is a scanning electron microscope (SEM) image of an active material composite particle according to various embodiments of the present disclosure, and FIG. 1b to 1d are cross-sectional views of core particles that may be included in the composite particle of FIG. 1a. Figures 2a, 2b, and 2c show Raman spectra for graphite and various graphene-based materials. Figure 3 shows the Raman spectra of typical carbon materials versus low-defect nemonic carbon I D / I G This is a bar chart comparing ratios. FIGS. 4a, 4b, and 4c show SiO2 encapsulated in amorphous carbon, reduced graphene oxide (rGO), and low-defect non-layered carbon, respectively. x Raman spectra of electrode active materials containing core particles are plotted. FIG. 5 is a graph showing the cycle life of an exemplary half-cell and a comparative half-cell containing lithium-metallated SiO (LM-SiO) according to various embodiments of the present disclosure. FIG. 6 is a graph showing the X-ray diffraction results of a control material versus a material of example (1) according to various embodiments of the present disclosure. Figure 7 is a graph showing the capacity retention rate of an exemplary cycled half-cell and a control half-cell containing magnesium-metallated SiO (MM-SiO). Figure 8 is a graph showing the anode capacities of the half-cells of Figure 7. Specific details for implementing the invention
[0012] Various embodiments are described in detail with reference to the attached drawings. Where possible, the same reference numbers will be used throughout the drawings to refer to identical or similar parts. References to specific examples and embodiments are for illustrative purposes only and are not intended to limit the scope or claims of the invention.
[0013] Where an element or layer is referred to as being "on" or "connected" to another element or layer, this may be understood to mean that it is directly on or directly connected to the other element or layer, or that an intervening element or layer may exist. In contrast, where an element is referred to as being "on" or "directly connected" to another element or layer, no intervening element or layer exists. For the purposes of this disclosure, it should be understood that "at least one of X, Y, and Z" may be interpreted as X only, Y only, Z only, or any combination of two or more of X, Y, and Z (e.g., XYZ, XYY, YZ, ZZ).
[0014] Where a range of values is provided, unless the context clearly indicates otherwise, each intermediate value between the upper and lower limits of the range and any other specified value or intermediate value within the specified range shall be understood to be included within the invention up to one-tenth of the lower limit unit. The upper and lower limits of such a narrower range may independently be included in the narrower range and are also included in the invention according to the limitations specifically excluded from the specified range. Where the specified range includes one or both of the limitations, the range excluding one or both of the included limitations is also included in the invention. Additionally, it should be understood that the term "about" may indicate a minor measurement error, for example, of + / - 5% to 10%.
[0015] Words such as "and then," "afterward," and "next" are not necessarily intended to restrict the order of steps, and may be used to guide the reader through descriptions of the method. Furthermore, referring to claim elements in the singular, for example using singular expressions, should not be interpreted as restricting the elements to the singular.
[0016] "Electrode material" is defined as a material that can be configured to be used as an electrode in an electrochemical cell, such as a lithium-ion rechargeable battery. "Electrode" is defined as the anode or cathode of an electrochemical cell. Additionally, "composite electrode material" is defined as comprising active material particles that are electrically conductive and combined with one of a particle, flake, sphere, platelet, sheet, tube, fiber, or a combination thereof. The particle, flake, sphere, platelet, sheet, tube, fiber, or a combination thereof may also be crushed, crumpled, wrinkled, layered, woven, braided, or a combination thereof.
[0017] The electrically conductive material may be selected from the group consisting of electrically conductive carbon-based materials, electrically conductive polymers, graphite, metallic powder, nickel, aluminum, titanium, stainless steel, and any combination thereof. The electrically conductive carbon-based material may further comprise one of graphite, graphene, diamond, pyrolytic graphite, carbon black, low-defect turbostratic carbon, fullerene, or a combination thereof. The "electrode material mixture" is defined as a combination of materials such as material particles (electrochemically active, electrically conductive, composites, or combinations thereof), binders or binders, non-crosslinked and / or crosslinked polymers or polymers, which are mixed together for use in forming electrodes for electrochemical cells, for example. In this specification, "electrochemically active material," "electrode active material," or "active material" is defined as a material that inserts and releases ions, such as ions in an electrolyte, to store and release electric potential. The terms "insert" and "release" may be further understood as ions that intercalate and deintercalate, or lithiate and delithiate.Therefore, the ion insertion and release processes are also understood as intercalation and extraction, or lithiation and delithiation. Accordingly, "active material," "electrochemical active material," or "active material particle" is defined as a material or particle capable of repeating ion insertion and extraction or lithium lithiation and delithiation.
[0018] A "defect" is defined as any feature that breaks the symmetry of the hexagonal lattice of carbon atoms in a given carbon sheet. According to this definition, defects may include changes in carbon hybridization, vacancies, substitutional atoms, edges, or grain boundaries. "Hybridization" refers to the formation of new orbitals by mixing standard atomic orbitals and can be used to describe molecular bonding. The mixing of standard atomic orbitals is generally sp² 2 and sp 3 It occurs in orbit.
[0019] Defect density is defined as the amount of symmetry-breaking features (defects) per given unit area of a carbon plane. This value is often estimated as the average distance between two defects. Defect density is I D / I G It can be approximated by Raman spectroscopy using ratios.
[0020] The "composite particle" may comprise one or more core particles comprising an electrochemical active material and a coating disposed on the surface of the core particles. The coating may comprise a carbon material, for example, pyroplastic carbon, carbon nanotubes, activated carbon, or any combination thereof.
[0021] According to various embodiments of the present disclosure, core particles are at least partially encapsulated (e.g., covered) by a coating. For example, the coating and / or the opaque carbon may cover, on average, about 10% to about 100%, e.g., about 20% to about 90%, about 25% to about 80%, about 30% to about 70%, or about 40% to about 60% of the surface of each core particle. In some embodiments, the coating may be in the form of an envelope or shell that at least partially or completely encapsulates at least one of the core particles.
[0022] In some embodiments, the coating may have a crumpled morphology. The term "crumpled" is defined as a volume or mass exhibiting a distribution of folds, ripples, undulations, wrinkles, and ridges. The term "crumpled" is also defined as being bent or bent. The term "morphology" is defined as the structure and features or characteristics of a surface. Specifically, "morphology" refers to the structure and features of the outer surface of particles or macroparticles of the electrode material.
[0023] As defined herein, a secondary electrochemical cell is a rechargeable electrochemical cell or battery. In this specification, "capacity" is defined as a measure of the charge stored by a battery, determined by the mass of the active material contained within the battery, representing the maximum amount of energy in ampere-hours (Ah) that can be extracted from the battery at rated voltage. Additionally, capacity may be defined by the formula (Capacity = Energy / Voltage or Current (A) x Time (h)). "Energy" is mathematically defined by the formula (Energy = Capacity (Ah) x Voltage (V)). In this specification, "specific capacity" is defined as the amount of charge that can be delivered for a specified time per unit of mass or per unit of volume of the active electrode material. Specific capacity may be measured in weight units, e.g., (Ah) / g, or volume units, e.g., (Ah) / cc. Specific capacity is defined by the mathematical formula (Specific Capacity (Ah / kg) = Capacity (Ah) / Mass (kg)). "Rate capability" is the ability of an electrochemical cell to receive or deliver a certain amount of energy within a specified time. Alternatively, "rate capability" is the maximum continuous or pulsed energy that a battery can provide per unit time.
[0024] In this specification, "C-rate" is defined as a measure of the rate at which a battery discharges relative to its maximum nominal capacity. For example, a 1C current rate means that the discharge current discharges the entire battery within 1 hour, a C / 2 rate means that the battery is completely discharged within 2 hours, and a 2C rate means that the battery is discharged within 0.5 hours. "Power" is defined as the rate of time for energy transfer measured in watts (W). Power is the product of the voltage (V) applied to the battery or cell and the current (A) passing through the battery or cell. Mathematically, "C-rate" is defined as C-rate (reciprocal of time) = Current (A) / Capacity (Ah), or C-rate (reciprocal of time) = 1 / Discharge time (h). Power is defined by the mathematical formula (Power (W) = Energy (Wh) / Time (h), or Power (W) = Current (A) x Voltage (V)). Coulomb efficiency is the efficiency of charge transfer within an electrochemical cell. Coulomb efficiency is the ratio of charge output to charge input by a battery.
[0025] Active material composite particles
[0026] Silicon and silicon alloys significantly increase battery capacity when incorporated into the electrodes of an electrochemical cell. Silicon and silicon alloys are often incorporated into electrodes containing graphite, graphene, or other carbon-based active materials. Examples of electrodes containing carbon-based materials and silicon are provided in U.S. Patents No. 8,551,650, No. 8,778,538 and No. 9,728,773 of the inventors (Kung et al.), the entire contents of which are incorporated herein by reference, and in U.S. Patents No. 10,135,059 and No. 10,135,063 of the inventors (Huang et al.).
[0027] In this specification, "SiO materials" may generally refer to silicon and oxygen-containing materials. SiO materials are materials of interest for use in the anode electrodes of lithium-ion batteries because they possess high theoretical energy and power densities. However, because they have low first-cycle efficiency and high irreversibility, for example, silicon oxide (e.g., SiO x The use of current commercial SiO materials, such as , where x is in the range of 0.8 to 1.2 (e.g., 0.9 to 1.1), has been limited. This low first-order cycle efficiency is due to high irreversible Li with the silicon oxide matrix. + It is due to the reaction.
[0028] Irreversible Li with silicon oxide +To reduce the reaction, various embodiments include metalized SiO materials (M-SiO). As specified herein, M-SiO materials may refer to active materials that react directly with an alkali and / or alkaline earth-containing precursor, such as a metal-containing precursor and / or a magnesium-containing precursor, to form a metalized silicon and oxygen-containing phase before being utilized as an active material in a battery and / or before undergoing charge-discharge reactions. In one embodiment, all or part of the metalized metal may remain within the active material and is not intercalated (i.e. inserted) or de-intercalated during battery charging and discharging. Thus, M-SiO materials may refer to lithium-metalized SiO (LM-SiO) materials and / or Mg-metalized SiO (MM-SiO) materials. However, in some embodiments, the M-SiO material may comprise a SiO material metallized to include other suitable alkali and / or alkaline earth metals, such as sodium, potassium, calcium, etc. For example, in some embodiments, the M-SiO material may be metallized to include magnesium, lithium, sodium, potassium, calcium, or any combination thereof.
[0029] The electrode material containing M-SiO active material has a first-cycle efficiency (1) compared to a non-metallic SiO material. stIt has been found to increase cycle efficiency (FCE). Unfortunately, M-SiO materials have been found to suffer from severe electrical disengagement and rapid capacity loss, often resulting in capacity degradation of over 90% within 20 cycles. Coating M-SiO materials with carbon and / or other materials, or blending M-SiO materials with graphite, has been found to slightly reduce electrical disengagement and capacity loss of the active material, delaying capacity degradation of over 50% to 50 cycles; however, this is still unsatisfactory cycle stability for commercial applications. Overall, current M-SiO materials do not exhibit sufficient electrical stability for commercialization.
[0030] FIG. 1a is a scanning electron microscope (SEM) image of an active material composite particle (100) according to various embodiments of the present disclosure, and FIG. 1b to 1d are cross-sectional views of core particles (102A to 102C) that may be included in the composite particle (100) of FIG. 1a. Referring to FIG. 1a and FIG. 1b, the composite particles (100) comprise a core particle (102) containing an electrochemical active material and a graphene-containing coating (110) coated on the core particle (102) and / or encapsulating the core particle (102).
[0031] In preferred embodiments, the active material of the core particle (102) comprises an M-SiO material. Accordingly, the composite particles (100) are described below in relation to the core particles (102) comprising the M-SiO material.
[0032] The composite particles (100) and / or core particles (102) may have an average particle size in the range of about 1 μm to about 20 μm, for example, about 2 μm to about 15 μm, about 3 μm to about 10 μm, about 3 μm to about 7 μm, or about 5 μm. The core particles (102) may comprise an M-SiO material comprising metallized silicon species and silicon (e.g., crystalline and / or amorphous silicon). The metallized silicon species may include metallized silicides and metallized silicates. In some embodiments, the M-SiO materials also include silicon oxide (SiO₂ x , where x may include a range of 0.8 to 1.2, e.g., 0.9 to 1.1). In various embodiments, M-SiO materials may include lithiated silicon species. In this specification, "lithiated silicon species" refers to lithium silicide (Li x It may include Si, 0 < x < 4.4) and / or one or more types of lithium silicates (Li2Si2O5, Li2SiO3, and / or Li4SiO4, etc.).
[0033] Referring to FIG. 1b, in some embodiments, the composite particles (100) may comprise heterogeneous core particles (102A) comprising an M-SiO material comprising a plurality of silicon-containing material phases (104, 106, 108). For example, the phases (104, 106, 108) are independently crystalline silicon, silicon oxide (e.g., SiO). x, where x may include silicon species in the range of 0.8 to 1.2, e.g., 0.9 to 1.1) and / or lithiated silicon species. However, in some embodiments, the core particles (102) may be substantially homogeneous particles comprising silicon, oxygen and lithium, although they lack distinct phases.
[0034] Referring to FIG. 1c, in some embodiments, the composite particles (100) may comprise core particles (102B) comprising a primary phase (120), wherein crystalline silicon domains (122) are dispersed as a secondary phase. For example, the primary phase (120) may comprise lithiated silicon species, such as lithium silicate species, particularly Li2Si2O5. In other embodiments, the primary phase (120) may comprise magnesium-metallated silicon species, magnesium silicate species, particularly MgSiO3, Mg2SiO4, or a combination thereof. The crystalline silicon domains (122) may comprise crystalline silicon nanoparticles having a particle size of less than 100 nm. For example, the crystalline silicon domains (122) may have an average particle size in the range of about 3 nm to about 60 nm. In one embodiment, most of the crystalline silicon domains (122) may have an average particle size in the range of about 5 nm to about 10 nm, and the remainder of the crystalline silicon domains (122) may have an average particle size in the range of about 10 nm to about 50 nm.
[0035] Referring to FIG. 1d, in some embodiments, the composite particles (100) comprise a primary phase (120) containing M-SiO material and, as a secondary phase, crystalline silicon domains (122) dispersed in the primary phase (120) and SiO x Domains (124) (e.g., SiO x, where x may include core particles (102C) comprising a range of 0.8 to 1.2, e.g., 0.9 to 1.1). For example, the primary phase (120) may include lithiated silicon species such as lithium silicate species, particularly Li2Si2O5, and the crystalline silicon domains (122) may include crystalline silicon nanoparticles, and SiO x The domains (124) are SiO x It may include phases and / or nanoparticles. Crystalline silicon domains (122) and SiO x The domains (124) may have a particle size of less than about 100 nm. For example, crystalline silicon domains (122) and SiO x The domains (124) may have an average particle size in the range of about 3 nm to about 60 nm, for example, in the range of about 5 nm to about 50 nm.
[0036] In various embodiments, the core particles (102) may represent about 80 weight% to about 99.5 weight%, for example, about 90 weight% to about 99 weight%, for example, about 90 weight% to 95 weight% of the total weight of the composite particles (100). In some embodiments, the M-SiO material may comprise about 40 at% to about 5 at%, for example, 20 at% to about 10 at%, or about 15 at% of lithiated silicon species. In some embodiments, the M-SiO material of the core particles (102A) comprises about 60 at% to about 95 at%, for example, about 80 at% to about 90 at%, or about 85 at% of silicon and SiO. xIt may include. The M-SiO material of the core particles (102) may have a silicon-to-oxygen atomic weight ratio of about 1.25:1 to about 1:1.25, for example, about 1.1:1 to about 1:1.1, or about 1:1. In some embodiments, the M-SiO material of the core particles (102) consists of crystalline silicon and SiO with nearly equal atomic weights. x It may include.
[0037] During the initial charging reaction and / or subsequent charging reactions, the composition of the M-SiO material of the core particles (102A) may change due to lithiation and / or other reactions. For example, Si and SiO x is Li x It can be lithiated to form Si domains. Also, some SiO x It can form inactive species such as lithium silicate and Li2O.
[0038] In various embodiments, the coating (110) may be in the form of a shell that completely encapsulates the core particles (102), as illustrated in FIGS. 1b through 1d. However, in some embodiments, the coating (110) may only partially encapsulate all or part of the core particles (102). In some embodiments, the coating (110) may represent about 0.5% to about 20% by weight, for example, about 1% to about 10% by weight, or about 5% to about 10% by weight of the total weight of the composite particles (100), based on the total weight of the composite particles.
[0039] In some embodiments, the coating (110) may comprise a flexible, high-conductivity graphene material, such as graphene, graphene oxide, partially reduced graphene oxide, or a combination thereof. For example, the coating (110) may comprise a flexible, high-conductivity graphene material having low-defect inlaid properties, which may preferably be referred to as inlaid carbon. The low-defect inlaid carbon may be in the form of a platelet comprising one to about 10 layers of a graphene material, such as graphene, graphene oxide, or reduced graphene oxide. In some embodiments, the low-defect inlaid carbon may comprise at least 90 weight%, for example, about 90 weight% to about 100 weight% of graphene. The graphene material may further comprise a powder, particles, a single-layer sheet, a multilayer sheet, a flake, a platelet, a ribbon, a quantum dot, a tube, a fullerene (a hollow graphene sphere), or a combination thereof.
[0040] The nambic carbon may be in the form of partially overlapping sheets or platelets to simulate larger single-sheet structures. In some embodiments, the platelets have one or more layers of graphene-based material. In some embodiments, the platelets may have a sheet size that is 15 μm or less on average. In some embodiments, the platelets may have a sheet size that is 1 μm or less on average. In some embodiments, the nambic carbon-based material platelets may have a thin thickness. In some embodiments, the thin thickness of the nambic carbon-based material platelets may be 1 μm or less on average. In some embodiments, the thin thickness of the nambic carbon-based material platelets may be 100 nm or less on average.
[0041] In addition to the graphene material, the coating (110) may include one or more additives, e.g., polymers, carbon nanotubes, activated carbon, and / or surfactants. In various embodiments, the coating (110) may also include lithium-containing species (e.g., LiF, etc.), alkali metal species, polymer coating species, amorphous carbon, and / or other conductive additives or formulations. For example, the conductive additives or formulations may include carbon black, KETJENBLACK, Super-P carbon black, low-defect non-layer carbon, acetylene black, channel black, furnace black, lamp black, thermal black, graphite, natural graphite, synthetic graphite, graphite oxide, partially reduced graphite, flake graphite, exfoliated graphite, platelet graphite, or a combination thereof. The conductive agent may also include one of a conductive fiber, carbon fiber, metal fiber, carbon nanotube (CNT), single-walled CNT, double-walled CNT, multi-walled CNT, metal powder, fluorocarbon powder, aluminum powder, nickel powder, nickel flake, conductive whisker, zinc oxide whisker, potassium titanate whisker, conductive metal oxide, titanium oxide, conductive organic compound, conductive polyphenylene derivative, conductive polymer, or a combination thereof.
[0042] For example, in some embodiments, the composite particles (100) may comprise, based on the total weight of the composite particles (100), about 0.5 wt% to about 19 wt%, for example, about 1 wt% to about 10 wt%, or about 5 wt% to about 10 wt% of infrastrated carbon, and 0 wt% to about 2 wt%, for example, about 0.25 wt% to about 1 wt%, or about 1 wt% of carbon nanotubes.
[0043] Due to its conductive properties, the coating (110) can ensure that the M-SiO material of the core (102) circulates homogeneously / uniformly in all three dimensions (movement of electrons and Li ions into and out of the structure), thereby minimizing stress applied to and caused by the core particles and minimizing particle breakage. Additionally, if the M-SiO material of the core is broken, the flexible coating (110) operates to electrically connect the broken M-SiO material and maintain the overall integrity of the composite particle (100), thereby significantly improving electrochemical performance.
[0044] For example, as described in detail below, graphene-containing coatings (110) were found to electrically stabilize the M-SiO material and increase cycle characteristics to over 300 cycles. Additionally, the coatings (110) were found to provide significantly improved electrical conductivity and higher primary cycle efficiency values of the M-SiO material compared to raw (e.g., uncoated) M-SiO material or M-SiO material coated with graphite and carbon black. In some embodiments, the electrode material containing the composite particles (100) can maintain over 90% of the available capacity after 20 cycles, which can increase the available cycle life by more than nine times.
[0045] Egg layer carbon
[0046] Figures 2a, 2b, and 2c illustrate the Raman spectra for graphite and various graphene-based materials. Graphite and graphene materials are approximately 1340 cm⁻¹. -1 , 1584 cm -1 and 2700 cm -1 It has been well established that it has a characteristic peak at 1340 cm⁻¹. -1 The peak at 1584 cm⁻¹ is shown in Fig. 2c and is characterized as the D band. -1The peak at is shown in the spectra of Figs. 2a and 2c, and the sp of all pairs 2 It is characterized by a G band originating from vibrational modes resulting from the stretching of C=C bonds of hybridized carbon atoms. The D band originates from hybridized vibrational modes associated with graphene edges and indicates the presence of defects or broken symmetry in the graphene structure. 2700 cm⁻¹ -1 The peak at is shown in Fig. 2b and is characterized by a 2D band resulting from a double resonance process caused by interactions between stacked graphene layers. The occurrence of a double peak at the 2D wavenumber breaks the symmetry of the peak and indicates an AB stacking order between graphite derivatives, such as nanoplatelets, and graphite graphene planes. The 2D1 peak shown in Fig. 1b is suppressed when the AB stacking order of turbostratic multilayer graphene particles is disrupted. The positions of the G and 2D bands are used to determine the number of layers in the material system. Thus, Raman spectroscopy provides scientific clarity and definition regarding carbon material additives for electrochemical cells, thereby providing a fingerprint for the correct selection as an additive to the active material electrode composition. As described, this definition provides a fingerprint for the low-defect turbostratic carbon of this application. It is this low-defect turbostratic carbon that provides excellent electrochemical cell performance when used as an additive in the electrode active material mixture of an electrochemical cell.
[0047] FIG. 3 shows the carbon additive (i.e., reduced graphene oxide or amorphous carbon) generally used in electrode active material mixtures of the prior art compared to the low-defect non-layered carbon of the present application. D / I G Provides a ratio.
[0048] Reduced graphene oxide (rGO) is a carbon variant often referred to as graphene in the industry, but its final structure and manufacturing process are unique. Graphene oxide is typically first prepared using a modified Hummers method, where graphite material is oxidized and exfoliated into single layers or platelets containing several carbon layers that may include, but are not limited to, hydroxyl, epoxide, carbonyl, and carboxyl functional groups. These functional groups are then removed through chemical or thermal treatment to convert the insulating graphene oxide into a conductive reduced graphene oxide. While reduced graphene oxide is similar to graphene in that it consists of single layers of carbon atomic lattices, it differs in that it features mixed sp2 and sp3 hybridization, residual functional groups, and often an increased defect density due to the manufacturing and reduction processes. Reduced graphene oxide is shown in the first bar of Fig. 3, and I D / I G The ratio is 0.9.
[0049] Amorphous carbon is often used as an additive or surface coating for both anode and cathode material mixtures in electrochemical cells to improve electrode conductivity. Typically, amorphous carbon is prepared using a chemical vapor deposition (CVD) process, where a hydrocarbon feedstock gas is introduced into a sealed vessel and carbonized onto the surface of the desired powder material at an elevated temperature. This pyrolysis process can provide a thin amorphous carbon coating several nanometers thick, free from any sp2 hybridization found in crystalline graphene-based materials. Amorphous carbon is shown in the third bar of Fig. 3, I D / I G The ratio is greater than 1.2.
[0050] Low-defect, non-layered carbon, also known as graphene, possesses unique properties derived from the manufacturing process. One common method for producing this material is to utilize a plasma-based CVD process in which a hydrocarbon feedstock gas is supplied through an inert gas plasma in the presence of a catalyst capable of nucleating graphene-like carbon structures. By controlling production parameters, carbon materials with several layers and no AB stacking order between lattices can be produced. These carbon materials are typically highly ordered sp2 carbon lattices with low defect density.
[0051] The low-defect egg-shaped carbon of the present disclosure is shown in the second bar in the center of FIG. 3. The Raman spectrum of the low-defect egg-shaped carbon additive of the present application is the ratio of the intensity of the D band to the G band (I D / I G ) and the intensity ratio of the 2D band to the G band (I 2D / I G It is derived from ). I D , I 2D , and I G It is expressed as the integrated strength of each of them. Low I D / I G The ratio indicates a low-defect material. The low-defect inlaid carbon material of the present invention is measured using an incident laser wavelength of 532 nm and, when determined by Raman spectroscopy, has an I greater than 0 and about 0.8 or less. D / I G It has a ratio, I G is 1580 to 1600 cm -1 It is in the wavenumber range, and I D is 1330 to 1360 cm -1 It is in the range of wavenumbers. In addition, the low-defect inlaid carbon material of the present disclosure has an I of about 0.4 or higher. 2D / I G Represents a ratio. 2D / I GAs a reference regarding the ratio, about 2 of I 2D / I G The ratio is generally associated with single-layer graphene. I of less than about 0.4 2D / I G The ratio generally relates to bulk graphite composed of multiple AB stacked graphene layers. Therefore, for the low-defect non-stacked carbon material of the present disclosure, I of about 0.4 or more 2D / I G The ratio indicates a small number of layers, less than 10. Low-defect, non-layered carbon materials with a small number of layers further lack AB stacking order between graphene layers (i.e., they are non-layered). The non-layered nature of these graphene planes, or the lack of AB stacking, is I 2D It is distinguished by the symmetry of the peaks. The symmetry of the 2D peaks distinguishes turbostratic graphene layered material and AB stacked graphene layered material, which represents rotational stacking disorder versus layered stacking order.
[0052] Carbon materials with high AB stacking order still exhibit 2D peaks, but these 2D peaks exhibit doublets that break the symmetry of the peaks. This breaking of symmetry occurs in both AB stacked graphene with several layers and graphite with many layers. Therefore, 2D peaks, which are a very strong indicator of the presence of stacking order regardless of the number of graphene layers present in the material, are important when selecting graphene or graphene-based additives. What distinguishes the low-defect inlaid carbon of the present disclosure from all other graphene or graphene-based additives used to date is the rotational disorder of the stacking in the low-defect inlaid carbon of the present disclosure, because the rotational disorder of the stacking in the low-defect inlaid carbon of the present application provides flexibility to the carbon-based particles of the present application, which enables the ability of these carbon-based particles to provide and preserve contact with active core particles of composite particles including electrodes of electrochemical cells. As a result, an electrochemical cell is produced that has increased cycle life, better cycle life stability, improved energy density, and excellent high-rate performance.
[0053] FIGS. 4a to 4c show SiO encapsulated or coated with carbon material. x Raman spectra for an active material mixture containing core particles are plotted. Fig. 4a shows SiO coated with an amorphous carbon material. x This is a graph of the Raman spectrum for an active material mixture containing core particles. Fig. 4b shows SiO encapsulated by rGO. x This is a graph of the Raman spectrum for an active material mixture containing core particles. Fig. 4c is a graph of SiO encapsulated by low-defect nemonic carbon. x This is a graph showing the Raman spectra for an active material mixture containing core particles. Each spectrum is for various layer thicknesses (wavelength 2700 cm⁻¹). -1Size, shape, and position of surrounding 2D peaks) and disorder (wavelength 1340 cm⁻¹ -1 It differs due to the size of the surrounding D peak.
[0054] Raman analysis sample preparation involves taking small aliquots of powders, such as active material powders, composite material powders, and carbon material powders, and placing these powders individually into clean glass vials. The sample powders are rinsed with methanol. Subsequently, the powder / methanol solution is briefly vortexed and sonicated for approximately 10 minutes. The suspension is transferred to a microscope slide using a micropipette. Afterward, the slide is completely air-dried before performing the analysis.
[0055] The Raman spectroscopic analysis of the present application was performed using confocal Raman spectroscopy on a Bruker Senterra Raman system under the following test conditions: 50 x 1000 μm aperture and 9 to 18 cm -1 Using resolution, a 532 nm laser, 0.02 mW, a 50x objective lens, a 90-second integration time, and three simultaneous additions (runs of three Raman spectroscopic samples). For reference, the D band is not activated in Raman scattering from perfect crystals. The D band becomes Raman active in defective graphite materials due to a defect-induced double-resonance Raman scattering process involving π-π electronic transitions. The intensity of the D band relative to the G band increases with the amount of disorder. Therefore, intensity I D / I G The ratio can be used to characterize graphene materials.
[0056] The D-band and G-band of amorphous carbon shown in Fig. 4a have higher intensities than the D-band and G-band of reduced graphene oxide (rGO) in Fig. 4b or the D-band and G-band of opaque carbon in Fig. 4c. Amorphous carbon also has substantially higher I than rGO and opaque carbon. D / I G It represents the ratio (1.25). The suppressed intensity of the G band of amorphous carbon compared to the intensity of the D band of amorphous carbon demonstrates a lack of crystallinity (also known as graphite properties) within the carbon structure of amorphous carbon. The D peak intensity being higher than the G peak intensity is caused by a large amount of defects within the amorphous carbon network structure. Therefore, the spectrum of amorphous carbon exhibits a much higher level of disorder and lower crystallinity in the graphite network structure compared to more crystalline carbon, such as graphene, graphene oxide, and rGO. Furthermore, the D peak intensity and G peak intensity of amorphous carbon and I D / I G Compared to the ratio, the intensity of the D peak of rGO and its G peak is higher, and its I D / I G A high ratio (almost twice) indicates that rGO has more defects than the layered carbon of the present application.
[0057] Table 1 below provides details regarding the Raman spectra of Figures 4a to 4c.
[0058] rGO D G 2D I D / I G I 2D / I G Cm -1 1346.98 1597.82 -- robbery 9115.5 10033.3 -- .91 -- Low-defect egg layer carbon D G 2D I D / I G I 2D / I G Cm -1 1346.92 1581.32 2691.9 robbery 2915.3 5849.98 6009.4 0.5 1.03 Amorphous carbon D G 2D I D / I G I 2D / I G Cm -1 1344.93 1589.40 2695.4 robbery 6194.8 4908.2 5238.5 1.25 1.07
[0059] Careful examination of these spectra reveals that as disorder increases, the D band broadens and the relative intensity of the band changes. For the sample coated with amorphous carbon, the high intensity (6194.8) and broad D peak indicate a large amount of defects. The G peak has a low intensity (4908.2), and the D peak (6194.8) indicates a lack of crystallinity. The D peak intensity (9115.5) and G peak intensity (10033.3) of the sample encapsulated by rGO are quite similar. However, it is noteworthy that the D peak intensity (9115.5) of the rGO sample is substantially higher than that of the pyroclastic carbon sample (2915.3), indicating that the rGO sample has a substantially higher defect density than the pyroclastic carbon sample. It is also noteworthy that for the amorphous carbon and rGO samples, the G band is at a wavelength of 1584 cm⁻¹. -1 Wavelength 1589.4 cm to the right -1 and 1597.82 cm -1 While they are shifted respectively up to [date], for the egg-stranded carbon sample, the G band is at a wavelength of 1584 cm -1 1581.32 cm, slightly to the left of -1 The important thing is that, unlike amorphous carbon and rGO samples, the nymphasized carbon (in this case, the graphene sample) does not exhibit many positional shifts (if present) reflecting low defects, so the nymphasized carbon sample is almost identical to a nearly 'perfect' nymphasized carbon material.
[0060] Composite particle formation
[0061] According to various embodiments, active material composite particles can be formed by forming a composite mixture comprising, for example, core particles of an active material such as an M-SiO active material, a graphene material, and optionally one or more additives such as CNTs, a dispersant, a binder, etc.
[0062] In particular, the composite mixture may comprise a composite suspension formed by initially mixing a first suspension comprising core particles dispersed in a polar solvent, for example, water or ethanol, and a second suspension comprising a graphene material dispersed in a polar solvent. The graphene material may comprise a difficult-to-layer carbon, for example, difficult-to-layer graphene. In various embodiments, the graphene material may comprise graphene, graphene oxide, partially reduced graphene oxide, or a combination thereof.
[0063] In some embodiments, the mixture may be stabilized by mixing and / or sonication until the mixture becomes visually homogeneous. For example, the initial mixture may be sonicated or high-shear mixed for about 30 to about 90 minutes, e.g., about 60 minutes, to increase suspension stability.
[0064] The first suspension may comprise about 0.5 wt% to about 10 wt%, for example, about 1 wt% to about 5 wt%, or about 2 wt% of M-SiO particles and the remainder of a solvent, based on the total weight of the first suspension. The second suspension may comprise about 0.5 wt% to about 10 wt%, for example, about 1 wt% to about 5 wt%, or about 2 wt% of graphene material and the remainder of a solvent, based on the total weight of the second suspension.
[0065] The amounts of the first and second suspensions used to form the composite mixture can be selected so that the composite mixture may have a core particle to carbon weight ratio in the range of about 80:20 to about 95:05, for example, in the range of about 90:10 to about 95:05. The composite mixture may be sonicated or high-shear mixed for about 30 minutes to about 90 minutes, for example, about 60 minutes, to increase suspension stability.
[0066] In some embodiments, CNTs may be optionally added directly to the first suspension or the second suspension, or to the composite mixture. For example, the amount of CNTs may be selected so that the composite mixture may have a core particle to CNT weight ratio of about 100:0 to about 95:3, for example, about 99.9:0.1 to about 99:1, or about 99:1.
[0067] The composite mixture can be processed so that the core particles are coated with graphene material and optionally CNTs. For example, the mixture can be dried using various processes, such as a spray-drying process, to produce a powder containing composite particles, for instance, core particles coated with carbon, for instance, pyrophylactoid carbon, or for instance, pyrophylactoid graphene, by evaporating the solvent. In particular, the composite mixture can be fed through a heated aerosol evaporator to evaporate the solvent and form the composite particles. This process can isotropically compress the graphene material through capillary forces that cause it to be completely crumpled, transforming it into a crumpled structure with countless folds, bends, and twists that do not relax over time.
[0068] Process parameters may vary depending on the requirements of the final powder particles. For example, crumpled spherical composite particles are formed by aerosolizing droplets and then rapidly drying them in a heating chamber. For instance, a sprayer sprays a suspension of raw materials to form aerosol droplets. During the spraying step, sufficient spray parameters are required to ensure that the particles within the droplets align before aerosol evaporation begins. In the case of non-layered carbon materials, particles within the droplets migrate to the surface of the droplets and form a coating on the M-SiO particles upon drying. These coatings minimize particle aggregation and agglomeration because this structure overcomes strong inter-particle van der Waals forces that cause the re-stacking of carbon material sheets, which complicates solution processability and reduces the accessible surface area of the particles. This structure is also stable against unfolding or collapsing.
[0069] Once the evaporation process is complete, the composite particles can be collected as a powder. After collection, the powder may be heat-treated in an inert atmosphere, such as argon gas, to carbonize residual surfactants or dispersants. In particular, the powder may be heated at a temperature in the range of about 600°C to about 800°C, for example, in the range of about 650°C to about 750°C, or at about 700°C. The heating process may have a heating ramp rate in the range of about 5°C / min to about 20°C / min, for example, about 10°C / min. Subsequently, the resulting dry composite active material powder may be classified by sieving or filtration to achieve a desired particle size distribution for a given application.
[0070] Alternatively, the composite mixture can be formed by dispersing core particles in a liquid solvent, for example, water or ethanol, to form a first suspension. Before or after adding the active material particles, a polyelectrolyte, such as polydiallyldimethylammonium chloride (PDDA), polyacrylic acid (PAA), or polysodium styrene sulfonate (PSS), is added to the solvent to form a primary surface charge on the active material particles, thereby allowing the active material particles to be stably suspended in the solvent. A second suspension can be formed by dispersing a carbon material (e.g., non-layered graphene powder) in a solvent, for example, water or ethanol. Before or after the addition of graphene, an oppositely charged polymer electrolyte is added to the solvent to form a secondary surface charge on the graphene, thereby allowing the graphene to be stably suspended in the solvent. The primary surface charge and the secondary surface charge may be different from positive and negative charges.
[0071] In some embodiments, the composite mixture may be formed by combining the first and second suspensions, and graphene may be attracted to the surface of the core particles due to the charge difference between them to form composite particles containing graphene-coated active material particles. The active material particles and the polymer electrolyte on the graphene neutralize each other, so that the composite particles may be substantially uncharged.
[0072] In various embodiments, the composite mixture may alternatively be formed by forming a dry mixture comprising a carbon material (e.g., non-layered graphene powder) and core particles but not containing a liquid solvent (i.e., the composite mixture is not a suspension). After a binding material is added to the mixture, a mechano-fusion process may be applied. In particular, the binding material may be physically mixed with the graphene powder and core particles to form composite particles, so that the core particles can be coated with graphene using a binder.
[0073] Non-restrictively binding materials include polymethyl methacrylate, polyethylene, polypropylene, polystyrene, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene terephthalate, polyacrylonitrile, polydiallyldimethylammonium chloride, polyacrylic acid, polyethylenetetrafluoroethylene (ETFE), lithiated polyacrylic acid (LiPAA), polysodium styrene sulfonate, polyvinylpyrrolidone, polyethylene glycol, polyethylene oxide, nylon, and carboxymethyl carboxymethyl cellulose, polysiloxanes, polyaramids, polyamides, polyimides, polyacrylates, polycarbonates, polyurethane, polyacetylene, polypyrrole, polyphenylene sulfid, poly(3,4-ethylenedioxythiophene), poly(1,3-dioxolane),Polyphenylene vinylene, polythiophene, polyaniline, polyfluorene, polypyrene, petroleum coke, coal tar pitch, carbon black, carbon nanotubes, sucrose, silica, indium tin oxide, aluminum-doped zinc oxide, lithium hydroxide, lithium acetate, lithium perchlorate, lithium fluoride, lithium nitride, lithium nitrate, lithium hexafluorophosphate, LiTFSI, LiFSI, NASICON, LISICON, LIPON, Li3PO4, Li7P3S, 11 It may include perovskites, garnets, polymerized ionic liquids, or any combination thereof.
[0074] In various embodiments, the amounts of particles of the M-SiO material and the carbon material, including low-defect nambique carbon, may be dry mixed in a dry weight ratio between 7:3 and 99:1. In some embodiments, CNTs may be added to the dry mixture. For example, the M-SiO material, the carbon material, and optionally CNTs may be combined to form a dry mixture that does not contain a liquid solvent or a wet mixture that contains a liquid solvent. For example, in some embodiments, the M-SiO material and the carbon material may be suspended in a polar liquid solvent such as water or ethanol by high-shear mixing or ultrasonic treatment. The suspension of some materials may also be facilitated by the use of surfactants and / or binders. Importantly, due to the high conductivity enabled by the low-defect nambique structure, the ratio of the material to be mixed with the electrochemical active material may be lower (less than 90:10 and even 99:1) compared to other carbon additives to achieve a similar conductivity enhancement.
[0075] Electrodes and Electrochemical Cells
[0076] According to various embodiments, composite particles can be used as an active material for an electrode, such as an anode, for example. For example, the composite particles can be mixed with a conductive agent, a binder and / or a solvent to form a slurry. The slurry can be coated onto a current collector to form an electrode.
[0077] The conductive agent may comprise a low-defect non-layered carbon material, carbon black, graphite, graphite oxide, graphene, exfoliated graphite or graphene, graphene oxide, rGO, partially reduced GO, carbon nanotubes such as single-wall, double-wall, or multi-wall carbon nanotubes (CNT), graphene platelets, nanoplatelets or nanoparticles, nanoplatelets or nanoparticles comprising one graphene sheet or several graphene sheets, or a combination thereof.
[0078] The electrode may comprise a composite material mixture capable of providing 100% of the anode lithium capacity, or may be mixed with other lithium active materials such as graphite, graphite oxide, graphene, graphene oxide, rGO, and partially reduced GO in a mixture of 0 to 100%. If the electrode comprises a binder to hold the electrode materials together, the binder may comprise a polymer material such as, for example, polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), CMC / SBR, polyacrylic acid (PAA), lithium polyacrylic acid (LiPAA), or a combination thereof. Subsequently, the electrode material components are mixed in a polar solvent such as water or N-methyl-2-pyrrolidone (NMP) with a solid load ranging from about 20% to about 60% by weight to form an electrode slurry.
[0079] Mixing is generally performed using a planetary mixer and a high-shear dispersion blade. Subsequently, the electrode slurry is coated onto a metal substrate, typically copper or aluminum, with an appropriate mass load to balance the lithium capacity of the anode and the selected cathode. Coating can be performed using various devices such as doctor blades, comma coaters, gravure coaters, and slot die coaters. After coating, the slurry is dried under forced air at a temperature between room temperature and about 120°C. Prior to battery assembly, the final electrode processing step includes pressing the electrode to reduce internal porosity and slitting it into an appropriate geometry. Typical anode compression density may range from about 1.0 g / cc to about 1.7 g / cc depending on the electrode composition and target application. Cathode compression density may be from about 2.7 to about 4.7 g / cc.
[0080] In various embodiments, the electrode is the anode electrode of an electrochemical cell, and the electrochemical cell also comprises a cathode and a non-aqueous electrolyte comprising a lithium salt. The anode comprises a metalloid or metal oxide material. The anode further comprises a low-defect inlaid carbon material. The anode may comprise composite particles. The composite particles may further comprise a spherical crumpled structure, and such crumpled structure comprises a low-defect inlaid carbon material encapsulating the metalloid or metal oxide material within its core. Alternatively, the anode may comprise a mixture of anode materials having particles comprising the metalloid or metal oxide material and particles comprising the inlaid carbon material. The inlaid carbon material may comprise low-defect inlaid carbon sheets that surround / encircle or are bonded to at least some of the core particles comprising the metalloid or metal oxide material. The cathode may comprise a carbon-based material. In addition to conventional carbon-based materials used for cathode electrodes of electrochemical cells, it is expected that the low-defect, non-layered carbon material of the present application can also be used as an additive for the cathode electrode of an electrochemical cell.
[0081] The structure of the electrochemical cell comprises a pairing of a coated anode substrate and a coated cathode substrate that are electronically separated from each other by a polymer and / or ceramic electrical insulating separator. The electrode assembly is sealed within a housing, which may be various structures such as, but not limited to, a coin cell, a pouch cell, or a can cell, and contains a non-aqueous ion-conducting electrolyte operably associated with the anode and cathode. The electrolyte consists of an inorganic salt dissolved in a non-aqueous solvent, more preferably an alkali metal salt dissolved in a mixture of a low-viscosity solvent comprising an organic ester, an ether, and a dialkyl carbonate, and a high-conductivity solvent comprising a cyclic carbonate, a cyclic ester, and a cyclic amide. Non-limiting examples of electrolytes include lithium hexafluorophosphate (LiPF6) or lithium bis(fluorosulfonyl)imide (LiFSi) salts in an organic solvent comprising one of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), fluoroethylene carbonate (FEC), or a combination thereof.Additional solvents useful in embodiments of the present invention include dialkyl carbonates, for example, tetrahydrofuran (THF), methyl acetate (MA), diglyme, triglyme, tetraglyme, 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), 1-ethoxy, 2-methoxyethane (EME), ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, and combinations thereof. High permittivity solvents that may also be useful include cyclic carbonates, cyclic esters, and cyclic amides, such as propylene carbonate (PC), butylene carbonate, acetonitrile, dimethyl sulfoxide, dimethyl formamide, dimethyl acetamide, gamma-valerolactone, gamma-butyrolactone (GBL), N-methyl-2-pyrrolidone (NMP), and combinations thereof. The electrolyte serves as a medium for the movement of lithium ions between the anode and cathode during the electrochemical reaction of the battery, particularly during the discharge and recharging of the battery. The electrochemical cell may also have a positive terminal and a negative terminal and / or contact structure.
[0082] Experimental Examples (Li-metallated SiO)
[0083] The following examples relate to anodes formed using anode active materials (e.g., composite particles) of various embodiments of the present disclosure and comparative anode active material particles, and are provided as examples, not limitations. In the examples, % is weight percent, g is gram, CE is Coulomb efficiency, and mAh / g is capacity. Additionally, the M-SiO active material used in the following formulations (1 to 4), examples (1 to 4), and control examples included lithium-metallated SiO (LM-SiO).
[0084] Formulation (1)
[0085] A composite active material of formula (1) was synthesized by suspending 2 grams of LM-SiO in 98 grams of water to prepare a 2 wt% suspension. The LM-SiO suspension was ultrasonically treated for 60 minutes to improve the stability of the suspension. After ultrasonically treating, 11.11 grams of a 2 wt% graphene suspension were added to the LM-SiO suspension to produce a homogeneous 2 wt% composite suspension. The ratio of LM-SiO to graphene suspension was selected so that the mass ratio was 90:10, which is LM-SiO:graphene. Subsequently, the composite suspension was ultrasonically treated for an additional 60 minutes. After ultrasonically treating, the composite suspension was supplied through a heated aerosol evaporator to evaporate the water and produce graphene-coated LM-SiO particles. After collecting the powder, the material was heat-treated at 700°C for 1 hour (heating ramp at 10°C / min) under an argon atmosphere to remove residues and carbonize the surfactant present in stabilizing the graphene suspension. Afterwards, the composite active material of the resulting formulation (1) was recovered.
[0086] Formulation (2)
[0087] A composite active material of formula (2) was synthesized by suspending 2 grams of LM-SiO in 98 grams of water to prepare a 2 wt% suspension. The LM-SiO suspension was ultrasonically treated for 60 minutes to improve the stability of the suspension. After ultrasonically treating, 11.11 grams of a 2 wt% graphene oxide (GO) suspension were added to the LM-SiO suspension to produce a homogeneous 2 wt% composite suspension. The ratio of LM-SiO to GO suspension was selected so that the mass ratio was 90:10, which is LM-SiO:reduced graphene oxide. Subsequently, the composite suspension was ultrasonically treated for an additional 60 minutes. After ultrasonically treating, the composite suspension was supplied through a heated aerosol evaporator to evaporate the water and produce graphene-coated LM-SiO particles. After collecting the powder, the material was heat-treated at 700°C for 1 hour (heating ramp at 10°C / min) under an argon atmosphere to remove residues and carbonize the surfactant present in stabilizing the graphene suspension. Afterwards, the composite active material of the resulting formulation (2) was recovered.
[0088] Formulation (3)
[0089] A composite active material of formula (3) was synthesized by suspending 2 grams of LM-SiO in 98 grams of water to prepare a 2 wt% suspension. The stability of the suspension was improved by ultrasonically treating the LM-SiO suspension for 60 minutes. After ultrasonically treating, 10.78 grams of a 2 wt% graphene suspension and 6.66 mg of carbon nanotubes (CNT) were added to the LM-SiO suspension to produce a homogeneous 2 wt% composite suspension. The ratio of LM-SiO to graphene suspension was selected such that the mass ratio was 90:9.7:0.3, which is LM-SiO:graphene:CNT. Subsequently, the composite suspension was ultrasonically treated for an additional 60 minutes. After ultrasonically treating, the composite suspension was supplied through a heated aerosol evaporator to evaporate the water and produce graphene-coated LM-SiO particles. After collecting the powder, the material was heat-treated at 700°C for 1 hour (heating ramp at 10°C / min) under an argon atmosphere to remove residues and carbonize the surfactant present in stabilizing the graphene suspension. Afterwards, the composite active material of the resulting formulation (3) was recovered.
[0090] Formulation (4)
[0091] A composite active material of formula (4) was synthesized by suspending 2 grams of LM-SiO in 98 grams of water to prepare a 2 wt% LM-SiO suspension. Additionally, 0.1 g of polymer dispersant was added to the suspension to improve stability. The LM-SiO suspension was sonicated for 60 minutes to improve the stability of the suspension. After sonication, 11.11 grams of a 2 wt% graphene suspension were added to the LM-SiO suspension to produce a homogeneous 2 wt% composite suspension. The ratio of LM-SiO to graphene suspension was selected so that the mass ratio was 90:10, which is LM-SiO:graphene. Subsequently, the composite suspension was sonicated for an additional 60 minutes. After sonication, the composite suspension was supplied through a heated aerosol evaporator to evaporate the water and produce graphene-coated LM-SiO particles. After collecting the powder, the material was heat-treated at 700°C for 1 hour (heating ramp at 10°C / min) under an argon atmosphere to remove residues and carbonize the surfactant present in stabilizing the graphene suspension. Afterwards, the composite active material of the resulting formulation (4) was recovered.
[0092] Control formulation
[0093] A control anode active material was produced by combining 0.5 grams of LM-SiO anode active material with 1.3 grams of graphite, 0.04 grams of a conductive agent (C65 carbon black), 7.72 grams of an aqueous binder (CMC 1.1 wt%), and 0.1875 grams of 40 wt% SBR in a small mixing container. Subsequently, the combined material was mixed thoroughly in an oil-based mixer for 30 minutes to form a control formulation slurry.
[0094] Contrast example
[0095] A control anode slurry was coated onto a copper foil having a loading of 3 mAh / cm2 and an electrode density of 1.3 g / cc. The coating was dried and calendered to a porosity of 40 to 45%. The electrode coatings were assembled into half-cells (excess counter electrode material = lithium metal), and 100 μL of electrolyte was injected into the cells. The cells were electrochemically "formed" under C / 20, C / 10, and C / 5 charge-discharge cycles. Subsequently, the resulting half-cells were characterized under a standard C / 2 charge-discharge protocol until the anode capacity reached 80% of the initial capacity.
[0096] Yes (1)
[0097] An anode material was produced by combining 0.5 grams of formulation (1) composite anode active material with 1.3 grams of graphite, 0.04 grams of a conductive agent (C65 carbon black), 7.72 grams of an aqueous binder (carbon methyl cellulose (CMC) 1.1 wt%) and 0.1875 grams of 40 wt% SBR in a small mixing container. Subsequently, the combined material was mixed thoroughly in an oil-type mixer for 30 minutes. The resulting anode slurry was coated onto a copper foil having a load of 3 mAh / cm2 and an electrode density of 1.3 g / cc. The coating was dried and calendared to a porosity of 40-45%. Electrode coatings were assembled onto half-cells (excess counter electrode material = lithium metal), and 100 μL of electrolyte was injected into the cells. The cells were electrochemically "formed" under C / 20, C / 10, and C / 5 charge-discharge cycles. Subsequently, the generated half-cells were characterized under a standard C / 2 charge-discharge protocol until the anode capacity reached 80% of the initial capacity.
[0098] Yes (2)
[0099] An anode material was produced by combining 0.5 grams of formulation (2) composite anode active material with 1.3 grams of graphite, 0.04 grams of conductive agent (C65 carbon black), 7.72 grams of aqueous binder (CMC 1.1 wt%) and 0.1875 grams of 40 wt% SBR in a small mixing container. Subsequently, the combined material was mixed thoroughly in an oil-type mixer for 30 minutes. The resulting anode slurry was coated onto a copper foil having a load of 3 mAh / cm2 and an electrode density of 1.3 g / cc. The coating was dried and calendered to a porosity of 40 to 45%. The electrode coatings were assembled into half-cells (excess counter electrode material = lithium metal) and 100 μL of electrolyte was injected into the cells. The cells were electrochemically "formed" under C / 20, C / 10, and C / 5 charge-discharge cycles. Subsequently, the generated half-cells were characterized under a standard C / 2 charge-discharge protocol until the anode capacity reached 80% of the initial capacity.
[0100] Yes (3)
[0101] An anode material was produced by combining 0.5 grams of formulation (3) composite anode active material with 1.3 grams of graphite, 0.04 grams of conductive agent (C65 carbon black), 7.72 grams of aqueous binder (CMC 1.1 wt%) and 0.1875 grams of 40 wt% SBR in a small mixing container. Subsequently, the combined material was mixed thoroughly in an oil-type mixer for 30 minutes. The resulting anode slurry was coated onto a copper foil having a load of 3 mAh / cm2 and an electrode density of 1.3 g / cc. The coating was dried and calendered to a porosity of 40 to 45%. The electrode coatings were assembled into half-cells (excess counter electrode material = lithium metal) and 100 μL of electrolyte was injected into the cells. The cells were electrochemically "formed" under C / 20, C / 10, and C / 5 charge-discharge cycles. Subsequently, the generated half-cells were characterized under a standard C / 2 charge-discharge protocol until the anode capacity reached 80% of the initial capacity.
[0102] Yes (4)
[0103] An anode material was produced by combining 0.5 grams of formulation (4) composite anode active material with 1.3 grams of graphite, 0.04 grams of conductive agent (C65 carbon black), 7.72 grams of aqueous binder (CMC 1.1 wt%) and 0.1875 grams of 40 wt% SBR in a small mixing container. Subsequently, the combined material was mixed thoroughly in an oil-type mixer for 30 minutes. The resulting anode slurry was coated onto a copper foil having a load of 3 mAh / cm2 and an electrode density of 1.3 g / cc. The coating was dried and calendered to a porosity of 40 to 45%. The electrode coatings were assembled into half-cells (excess counter electrode material = lithium metal) and 100 μL of electrolyte was injected into the cells. The cells were electrochemically "formed" under C / 20, C / 10, and C / 5 charge-discharge cycles. Subsequently, the generated half-cells were characterized under a standard C / 2 charge-discharge protocol until the anode capacity reached 80% of the initial capacity.
[0104] FIG. 5 is a graph showing the electrochemical cycling performance of half-cells formed using a control formulation (control) and formulations (1 to 4) (examples (1 to 4)). As will be described in detail below, the anodes of the control half-cells contained 25 wt% of bare LM-SiO material, and the anodes of the half-cells of examples (1 to 4) each contained 25 wt% of graphene-coated LM-SiO material of formulations (1 to 4). The anodes of the control half-cells and the half-cells of examples (1 to 4) also contained 65 wt% graphite, 2 wt% C65, 4.25 wt% CMC, and 3.75 wt% styrene-butadiene rubber (SBR).
[0105] Table 2 below includes the electrochemical cycling performance of the half-cells shown in Fig. 5.
[0106]
[0107] Table 3 below contains the electrochemical cycling values of the half-cells shown in Fig. 5.
[0108] substance Initial capacity (mAh / g) Capacity retention rate (50th cycle) Improvement in retention rate (50th cycle) Control (25% LM-SiO) 570 43% --- Formulation (1) (25% LM-SiO) 586 72% 67% Formulation (2) (25% LM-SiO) 553 79% 84% Formulation (3) (25% LM-SiO) 567 84% 95% Formulation (4) (25% LM-SiO) 571 74% 72%
[0109] As can be seen in FIG. 5, Table 2 and Table 3, after 50 charge / discharge cycles, compared to half-cells containing a control material, half-cells containing formulation (1) material showed a cycle life of 67%, half-cells containing formulation (2) material showed a cycle life of 84%, half-cells containing formulation (3) material showed a cycle life of 95%, and half-cells containing formulation (4) material showed a cycle life of 72%.
[0110] Accordingly, the composite particles of the present invention unexpectedly and significantly increased the available cycle life of LM-SiO materials for commercial lithium-ion battery applications. This improved available cycle life is due to the unexpected and non-trivial ability of graphene to stabilize lithium-containing SiO active materials through electrochemical cycling. Available cycle life is defined as the number of cycles (cycle n) in which a battery can be cycled while maintaining a capacity of at least 80% of its initial capacity (i.e., cycle 1). For example, formulation (4) exhibited a half-cell cycle life of about 50 cycles (n=50) for maintaining 80% capacity (cycle 1 to 600 mAh / g initial capacity, thus 480 mAh / g = 80% capacity). In contrast, the control material exhibited a half-cell cycle life of only 5 cycles for maintaining 80% capacity.
[0111] According to the embodiments, the battery has a 50th cycle capacity retention rate of at least 72%, for example, 80 to 84%, and a first cycle efficiency of at least 87%, for example, 87 to 88.6%.
[0112] Figure 6 is a graph showing the X-ray diffraction results of a control material (indicated in gray) compared to the material of example (1) (indicated in black). As can be seen in Figure 6, no change in particle crystallinity or structure was observed due to graphene addition and treatment.
[0113] Experimental Examples (Mg-Metallic SiO)
[0114] The following examples relate to anodes formed using anode active materials (e.g., composite particles) of various embodiments of the present disclosure and comparative anode active material particles, and are provided as examples, not limitations. In the examples, % is weight percent, g is gram, CE is Coulomb efficiency, and mAh / g is capacity. Additionally, the M-SiO active material used in the formulation (5), example (5), and control example below included magnesium-metallated SiO (LM-SiO).
[0115] Formulation (5):A composite active material of formula (5) was synthesized by suspending 2 grams of MM-SiO (i.e., magnesium-containing silicon oxide) in 98 grams of water to prepare a 2 wt% suspension. The stability of the MM-SiO suspension was improved by ultrasonically treating it for 60 minutes. After ultrasonically treating, 5.05 grams of a 2 wt% graphene suspension and 4.21 mg of carbon nanotubes (CNT) were added to the MM-SiO suspension to produce a homogeneous 2 wt% composite suspension. The ratio of MM-SiO to graphene suspension was selected such that the mass ratio was MM-SiO:graphene:CNT of 95:4.8:0.2. Subsequently, the composite suspension was ultrasonically treated for an additional 60 minutes. After ultrasonically treating, the composite suspension was fed through a heated aerosol evaporator to evaporate the water and produce graphene-coated MM-SiO particles. After collecting the powder, the material was heat-treated at 700°C for 1 hour (heating lamp at 10°C / min) under an argon atmosphere to remove residues and carbonize the surfactant present in stabilizing the graphene suspension. Afterwards, the composite active material of the resulting formulation (5) was recovered.
[0116] Yes (5):An anode material was produced by combining 0.5 grams of formulation (5) composite anode active material with 0.033 grams of conductive agent (C65 carbon black) and 1.33 grams of aqueous binder (LiPAA, 10 wt%) in a small mixing container. Subsequently, the combined material was mixed thoroughly in an oil-type mixer for 30 minutes. The resulting anode slurry was coated onto a copper foil having a load of 3 mAh / cm2 and an electrode density of 1.3 g / cc. The coating was dried and calendered to a porosity of 40 to 45%. The electrode coatings were assembled into half-cells (excess counter electrode material = lithium metal) and 100 μL of electrolyte was injected into the cells. The cells were electrochemically "formed" under C / 20, C / 10, and C / 5 charge-discharge cycles. Subsequently, the generated half-cells were characterized under a standard C / 2 charge-discharge protocol until the anode capacity reached 80% of the initial capacity.
[0117] MM-SiO Contrast Example: An anode material was prepared by combining 0.5 grams of MM-SiO anode active material with 0.033 grams of a conductive agent (C65 carbon black) and 1.33 grams of an aqueous binder (LiPAA, 10 wt%) in a small mixing vessel. Subsequently, the combined material was thoroughly mixed in an oil-based mixer for 30 minutes. The resulting anode slurry was coated onto a copper foil having a load of 3 mAh / cm2 and an electrode density of 1.3 g / cc. The coating was dried and calendered to a porosity of 40 to 45%. The electrode coatings were assembled into half-cells (excess counter electrode material = lithium metal), and 100 μL of electrolyte was injected into the cells. The cells were electrochemically "formed" under C / 20, C / 10, and C / 5 charge-discharge cycles. Subsequently, the generated half-cells were characterized under a standard C / 2 charge-discharge protocol until the anode capacity reached 80% of the initial capacity.
[0118] FIG. 7 is a graph showing the capacity retention rate of cycled half-cells including the MM-SiO material of formulation (5) and an MM-SiO control example, and FIG. 8 is a graph showing the anode capacity of the cycled half-cells of FIG. 7. Referring to FIG. 7 and FIG. 8, it can be seen that formulation (5) provides significantly superior anode capacity and capacity retention rate compared to the MM-SiO control example.
[0119] Although the foregoing describes specific preferred embodiments, it will be understood that the invention is not so limited. It will be obvious to those skilled in the art that various modifications may be made to the disclosed embodiments and that such modifications are intended to be within the scope of the invention. All publications, patent applications, and patents cited herein are incorporated herein by reference in their entirety.
Claims
Claim 1 Composite particles of active material for a lithium-ion secondary battery, wherein each of the composite particles comprises: a core particle comprising an alkali metal or alkaline earth metal silicate; and a coating disposed on the surface of the core particle; wherein the coating comprises turbostratic carbon, and the turbostratic carbon is: 1330 cm -1 to 1360 cm -1 Peak intensity (I) at wave numbers between D D band having ); 1580 cm -1 up to 1600 cm -1 Peak intensity (I) at wavenumbers between G G band having ); and 2650 cm -1 to 2750 cm -1 Peak intensity (I) at wavenumbers between 2D 2D band having ); having a Raman spectrum having , wherein I D / I G The ratio of is in the range of greater than 0 to 1.1, and I 2D / I G Composite particles, the ratio of which is in the range of 1.03 to 2. Claim 2 Composite particles according to claim 1, wherein the core particles represent 80% to 99.5% by weight of the total weight of the composite particles, the coating represents 0.5% to 20% by weight of the total weight of the composite particles, and the infertile carbon represents 1% to 10% by weight of the total weight of the composite particles. Claim 3 Composite particles according to claim 1, wherein 90% to 100% by weight of the layered carbon is in the form of a platelet comprising 1 to 10 sheets of graphene, and the coating further comprises 0.1% to 1% by weight of carbon nanotubes (CNT) based on the total weight of the composite particles. Claim 4 In claim 1, composite particles, wherein at least some of the core particles are completely encapsulated by a corresponding coating. Claim 5 In claim 1, composite particles, wherein at least some of the core particles are partially encapsulated by a corresponding coating. Claim 6 In claim 1, the composite particles are composite particles having an average particle size in the range of 3 μm to 10 μm. Claim 7 Composite particles according to claim 1, wherein the core particle comprises: a primary phase comprising Li2Si2O5, Li2SiO3, Li4SiO4, or any combination thereof; and crystalline silicon domains dispersed within the primary phase. Claim 8 In claim 7, the core particles are SiO dispersed within the primary phase. x Composite particles comprising additional domains, wherein x is in the range of 0.8 to 1.
2. Claim 9 In claim 7, the primary phase comprises Li2Si2O5, and the crystalline silicon domains have an average particle size of less than 100 nm, forming composite particles. Claim 10 Composite particles according to claim 1, wherein the core particles comprise: a primary phase comprising MgSiO3, Mg2SiO4, or a combination thereof; and crystalline silicon domains dispersed within the primary phase. Claim 11 In claim 1, I D / I G The ratio of is in the range of 0.3 to 0.7, and I 2D / I G The ratio of is in the range of 0.8 to 1.2, and I D is 1340 cm -1 In the watch of, I G is 1584 cm -1 It is in the watch of, and I 2D is 2700 cm -1 Composite particles in the wavenumber of. Claim 12 An electrode comprising, as an electrode, the composite particles of claim 1; and a binder. Claim 13 In claim 12, the binder comprises: polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), poly(acrylic) acid, polyethylenetetrafluoroethylene (ETFE), polyamides, and polyimides, polyethylene, carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyacrylic acid (PAA), lithium polyacrylic acid (LiPAA), or a mixture thereof, and the electrode further comprises a conductive additive selected from the group consisting of carbon black, carbon nanotubes, electrically conductive polymers, graphite, metal powders, nickel, aluminum, titanium, stainless steel, and any combination thereof. Claim 14 A lithium secondary battery comprising: an anode including the electrode of claim 12; a cathode; an electrolyte disposed between the anode and the cathode; and a housing that seals the anode, the cathode and the electrolyte, wherein the battery has a 50th cycle capacity retention rate of at least 72% and a first cycle efficiency of at least 87%. Claim 15 A method for forming active material composite particles, comprising: forming a mixture comprising core particles comprising an alkali metal or alkaline earth metal silicate and a pyroclastic carbon; and treating the mixture to form composite particles comprising the core particles coated with the pyroclastic carbon; wherein the pyroclastic carbon is: 1330 cm -1 to 1360 cm -1 Peak intensity (I) at wavenumbers between D D band having ); 1580 cm -1 up to 1600 cm -1 Peak intensity (I) at wavenumbers between G G band having ); and 2650 cm -1 to 2750 cm -1 Peak intensity (I) at wavenumbers between 2D 2D band having ); having a Raman spectrum having , wherein I D / I G The ratio of is in the range of greater than 0 to 0.8, and I 2D / I G A method in which the ratio is in the range of 1.03 to 2. Claim 16 delete Claim 17 delete Claim 18 delete Claim 19 delete Claim 20 delete
Citation Information
Patent Citations
Negative electrode active substance for non-aqueous electrolyte secondary battery, negative electrode for non-aqueous electrolyte secondary battery, non-aqueous electrolyte secondary battery, and method for producing negative electrode material for non-aqueous electrolyte secondary battery
KR1020180018552A
Silicon oxide composite for anode material of secondary battery and method for preparing the same
KR1020180106485A
Composite, its preparation method and use in lithium-ion secondary batteries
KR1020190040318A
